Utility of the Measurement of Carboxyhemoglobin Level at the Site of Acute Carbon Monoxide Poisoning in Rural Areas - Makoto Onodera; Yasuhisa Fujino; Satoshi Kikuchi; Masayuki Sato; Kiyofumi Mori; Takaaki Beppu; Yoshihiro Inoue (Scientifica)
Objective. This study examined the hypothesis that correlations exist between the carbon monoxide exposure time and the carboxyhemoglobin concentration at the site of carbon monoxide poisoning, using a pulse carbon monoxide oximeter in rural areas or the carboxyhemoglobin concentration measured at a given medical institution. Background. In previous studies, no definitive relationships between the arterial blood carboxyhemoglobin level and the severity of carbon monoxide poisoning have been observed. Method. The subjects included patients treated for acute carbon monoxide poisoning in whom a medical emergency team was able to measure the carboxyhemoglobin level at the site of poisoning. We examined the relationship between the carboxyhemoglobin level at the site of poisoning and carbon monoxide exposure time and the relationships between the arterial blood carboxyhemoglobin level and carbon monoxide exposure time. Results. A total of 10 patients met the above criteria. The carboxyhemoglobin levels at the site of poisoning were significantly and positively correlated with the exposure time (rs = 0.710, p=0.021), but the arterial blood carboxyhemoglobin levels were not correlated with the exposure time. Conclusion. In rural areas, the carboxyhemoglobin level measured at the site of carbon monoxide poisoning correlated with the exposure time.